PENINGKATAN KEMAMPUAN TENAGA PENDIDIK DI RA. AL FARIQ DALAM BIDANG TEKNOLOGI INFORMASI - Handayani, Masitah; Irawati, Novica; Larasati, Mustika Fitri; Helmiah, Fauriatun; Sari, Ade Mutiara (Smart Education, 2025)
Abstract: The rapid development of information technology has brought significant changes in the world of education. The ability of educators to master information technology is an important factor in improving the quality of learning. Information technology not only facilitates access to learning resources, but also enables more innovative and interactive learning methods. However, many educators still face obstacles in utilizing information technology, such as limited skills in using learning software, lack of adequate training, and limited access to technological facilities. This hinders the optimization of the use of technology in the teaching and learning process. Therefore, improving the ability of educators in the field of information technology is a must so that they can adapt to the times and create a more effective and interesting learning experience for students. Through appropriate training and mentoring, educators are expected to be able to integrate information technology into the learning process optimally. Keywords: Educators, Technology, Information Abstrak: Perkembangan teknologi informasi yang pesat telah membawa perubahan signifikan dalam dunia pendidikan. Kemampuan tenaga pendidik dalam menguasai teknologi informasi menjadi faktor penting dalam meningkatkan kualitas pembelajaran. Teknologi informasi tidak hanya mempermudah akses terhadap sumber belajar, tetapi juga memungkinkan metode pembelajaran yang lebih inovatif dan interaktif. Namun, masih banyak tenaga pendidik yang menghadapi kendala dalam pemanfaatan teknologi informasi, seperti keterbatasan keterampilan dalam menggunakan perangkat lunak pembelajaran, kurangnya pelatihan yang memadai, serta keterbatasan akses terhadap sarana teknologi. Hal ini menghambat optimalisasi penggunaan teknologi dalam proses belajar mengajar. Oleh karena itu, peningkatan kemampuan tenaga pendidik dalam bidang teknologi informasi menjadi suatu keharusan agar mereka dapat beradaptasi dengan perkembangan zaman dan menciptakan pengalaman belajar yang lebih efektif dan menarik bagi peserta didik. Melalui pelatihan dan pendampingan yang tepat, tenaga pendidik diharapkan mampu mengintegrasikan teknologi informasi dalam proses pembelajaran secara optimal. Kata Kunci: Tenaga Pendidik, Teknologi, Informasi